Statistical Modeling on the Risk Factors of Pneumonia - Virgelio M. Alao; Anthony D. Bartolore (Philippine Social Science Journal, 2022)
In our world today, pneumonia is among the common diseases that cause difficulty in breathing for humans. In the Philippines, it is one of the deadliest diseases that cut off the life of the citizens. Its direct or indirect negative effects threaten the health and life expectancy of human beings. This study determines the risk factors of pneumonia by applying Binary Logistic Regression then developing a model to estimate the probability that an individual may acquire pneumonia based on his or her medical and non-medical records. Results showed that the best fitting model contains eight risk factors, namely, Pulmonary Tuberculosis (PTB), Bronchitis, Chronic Obstructive Pulmonary Disease (COPD), duration of hospital stay, age, acute gastritis, cerebral infarction, and dehydration. The first four risk factors and age (at least 65 years) increase the odds of having pneumonia, while the last three risk factors decrease the odds of having pneumonia.